Reproduccion vegetativa de materiales para la siembra libres de enfermedades - Roca, W. (International Center for Tropical Agriculture, 1981)
Methods of vegetative reproduction are discussed using the results obtained with cassava and potato. Results of clone cleaning by heat therapy and in vitro meristem culture are given. Two methods for rapid cassava multiplication are proposed: by sprouts from cuttings and single leaf cuttings, which are able to produce 36,000 and 300,000 commercial cuttings/yr, resp. Finally, in vitro multiplication methods that assure max. cleanness of propagative material are given. (AS)